Analisis Pelayanan Prima Daya Tarik Wisata Air Terjun Bayang Sani Kecamatan Bayang Kabupaten Pesisir Selatan - Effendi, Aqila; Putra, trisna; Pidianti, Ema (Departemen Pariwisata Universitas Negeri Padang, 2025)
This research is motivated by several problems encountered and related to excellent service at the Bayang Sani Waterfall Tourist Attraction, Bayang District, such as: officers who are still not dressed, which indicates that the manager of the tourist attraction has also not used identification marks, still lack of attention to tourist satisfaction. when traveling such as regarding the cleanliness of the tourist attraction area. This study aims to determine how the analysis of excellent service from the manager of the Bayang Sani Waterfall tourist attraction in terms of the 6A excellent service concept, namely: ability, attitude, appearance, attention, action, accountability. The sampling method used in this study is non-probability sampling with sampling using purposive sampling. In this study, the criteria to be used are people who have visited the tourist attraction of Bayang Sani Waterfall who are 25 years old and above. Using the respondent achievement technique (TCR) as a data analysis technique and distributing questionnaires as a data collection technique made with a Likert scale. The results indicated that: (1) The ability indicator with a TCR percentage of 62.58% and the category was not good. (2) Attitude indicator with a TCR percentage of 62.51% and the category is not good. (3) The appearance indicator with a TCR percentage of 47.48% and the category is not good. (4) Attention indicator with a TCR percentage of 59.62% and the category is not good. (5) Action indicators with a TCR percentage of 62.32% and the category is not good (6) Last, accountability indicators with a TCR percentage of 61.00% and not good category.